2022
DOI: 10.1002/alz.12841
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and CSF biomarkers in a memory clinic: Head‐to‐head comparison of phosphorylated tau immunoassays

Abstract: Introduction: Direct comparisons of the main blood phosphorylated tau immunoassays in memory clinic populations are needed to understand possible differences. Methods:In the BIODEGMAR study, 197 participants presenting with cognitive complaints were classified into an Alzheimer's disease (AD) or a non-AD cerebrospinal fluid (CSF) profile group, according to their amyloid beta 42/ phosphorylated tau (Aβ42/p-tau) ratio. We performed a head-to-head comparison of nine plasma and nine CSF tau immunoassays and deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 41 publications
4
78
0
Order By: Relevance
“…In Down syndrome, plasma p-tau181 correlated with atrophy and hypometabolism in temporoparietal regions [54]. When more than one p-tau form was included in a study, plasma p-tau217 generally showed stronger associations with brain Aβ deposition than p-tau181 and p-tau231 [49,62,68,69,71]. Moreover, the IP-MS plasma p-tau217 method performed better than immunoassaybased ones in a recent comparative study [68].…”
Section: Plasma P-tau Associations With Clinical and Biological Evide...mentioning
confidence: 99%
“…In Down syndrome, plasma p-tau181 correlated with atrophy and hypometabolism in temporoparietal regions [54]. When more than one p-tau form was included in a study, plasma p-tau217 generally showed stronger associations with brain Aβ deposition than p-tau181 and p-tau231 [49,62,68,69,71]. Moreover, the IP-MS plasma p-tau217 method performed better than immunoassaybased ones in a recent comparative study [68].…”
Section: Plasma P-tau Associations With Clinical and Biological Evide...mentioning
confidence: 99%
“…Several publications have highlighted that a mass spectrometry measurement of Aβ peptides is more reflective of cerebral Aβ than immunoassay methods . We also acknowledge that there is a range of diagnostic performance in different p-tau measurements in determining AD …”
Section: Discussionmentioning
confidence: 99%
“…3,34 We also acknowledge that there is a range of diagnostic performance in different p-tau measurements in determining AD. 2,35…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These performances have been independently authenticated in dozens of research cohorts, with some studies further showing that plasma p-tau measures correlate well with CSF p-tau in paired samples [1,4,44]. Moreover, plasma p-tau often performs equivalently to CSF p-tau to differentiate Aβ-positive AD dementia individuals from Aβ-negative non-AD dementia and control participants [16 ▪▪ ,47 ▪▪ ]. The specificity of plasma p-tau to AD pathophysiology (compared with other biomarkers like NfL and GFAP) makes it a potential first line of action in the diagnostic workup [1,2].…”
Section: Diagnostic and Prognostic Performances Suggesting That Blood...mentioning
confidence: 96%